Political legal framework of party wings in mobilizing young voters in the digital era - Arifin, Firdaus (Institute Of computer Science (IOCS), 2024)
In the digital age, political party wing organizations increasingly rely on digital strategies to mobilize young voters; however, legal policies regulating technology use can both support and hinder their effectiveness. This study aims to analyze the impact of legal policies on the implementation of digital strategies in political campaigns. The research employs normative legal analysis with a qualitative approach, reviewing regulations on data privacy, digital political advertising, and political funding. Based on the research findings, it is evident that regulations supporting transparency and compliance play a crucial role in managing data and enhancing public trust. However, overly stringent regulations can reduce the flexibility and effectiveness of the digital strategies employed by political party wings. Therefore, it is essential to implement balanced policies that not only foster innovation but also safeguard individual rights.